Assessment of the Physicochemical Qualities and Prevalence of Escherichia coli and Vibrios in the Final Effluents of Two Wastewater Treatment Plants in South Africa: Ecological and Public Health Implications - Olayinka Osuolale (International Journal of Environmental Research and Public Health, 2015)
The final effluents of two wastewater treatment plants (WWTPs) in the Eastern Cape Province of South Africa were evaluated for their physicochemical and microbiological qualities over a period of 12 months. The physicochemical parameters assessed ranged as follows both plants. The ranges of values for the physicochemical are: pH (3.9–8.6), total dissolved solids (86.50–336.3 mg/L), electrical conductivity (13.57–52.50 mS/m), temperature (13–28 °C), nitrate (0–21.73 mg/L), nitrite (0.01–0.60 mg/L), orthophosphate (1.29–20.57 mg/L), turbidity (4.02–43.20 NTU), free chlorine (0.05–7.18 mg/L), dissolve oxygen (3.91–9.60 mg/L), biochemical oxygen demand (0.1–9.0 mg/L) and chemical oxygen demand (4.67–211 mg/L). The microbiological assessment for both WWTPs revealed the presence of E. coli in counts ranging between 0 and 1.86 × 104 CFU/100 mL and Vibrio counts ranging between 0 and 9.93 × 103 CFU/100 mL. We conclude that these WWTPs are important point sources of pollution in surface water with potential public health and ecological risks.